2016
DOI: 10.1038/npjqi.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Quantum gate learning in qubit networks: Toffoli gate without time-dependent control

Abstract: We put forward a strategy to encode a quantum operation into the unmodulated dynamics of a quantum network without the need for external control pulses, measurements or active feedback. Our optimisation scheme, inspired by supervised machine learning, consists in engineering the pairwise couplings between the network qubits so that the target quantum operation is encoded in the natural reduced dynamics of a network section. The efficacy of the proposed scheme is demonstrated by the finding of uncontrolled four… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 61 publications
1
70
0
Order By: Relevance
“…Indeed, in Ref. [7] it was shown that both the Toffoli gate and Fredkin gate can be carried out with high fidelity by unmodulated interactions, even when one is restricted to physical two-body couplings between qubits. The procedure for learning the correct physical Hamiltonian that reproduces the given target gate was called quantum gate learning [7,37], while the resulting architecture was called while-you-wait computing [7].…”
Section: B Quantum Gate Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, in Ref. [7] it was shown that both the Toffoli gate and Fredkin gate can be carried out with high fidelity by unmodulated interactions, even when one is restricted to physical two-body couplings between qubits. The procedure for learning the correct physical Hamiltonian that reproduces the given target gate was called quantum gate learning [7,37], while the resulting architecture was called while-you-wait computing [7].…”
Section: B Quantum Gate Learningmentioning
confidence: 99%
“…For this reason, SGD was also used in [7] for obtaining a quantum network that accurately approximates a Toffoli gate. SGD has some benefits: it is fast and has the ability to escape, in principle, from some local minima.…”
Section: Differential Evolutionmentioning
confidence: 99%
See 3 more Smart Citations